2003
DOI: 10.1073/pnas.1030231100
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of defective DNA mismatch repair and MSH6 mutation in an unselected series of endometrial cancers

Abstract: Endometrial cancer is the most common gynecologic malignancy in the United States and the most frequent extracolonic tumor in hereditary nonpolyposis colorectal cancer (HNPCC). HNPCC patients have inherited defects in DNA mismatch repair and the microsatellite instability (MSI) tumor phenotype. Sporadic endometrial cancers also exhibit MSI, usually associated with methylation of the MLH1 promoter. Germ-line MSH6 mutations, which are rare in HNPCC, have been reported in several families with multiple members af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
142
2
5

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 211 publications
(161 citation statements)
references
References 20 publications
10
142
2
5
Order By: Relevance
“…Further and larger samples study need to identify the association and the role of polymorphism I219V in carcinogenesis. Epigenetic silencing of the MLH1 gene is one of the most common causes of DNA mismatch repair capacity deficiency (Goodfellow et al, 2003). Some study has indicated that the SNP -93G>A may increase the susceptibility of the promoter sequence to methylation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further and larger samples study need to identify the association and the role of polymorphism I219V in carcinogenesis. Epigenetic silencing of the MLH1 gene is one of the most common causes of DNA mismatch repair capacity deficiency (Goodfellow et al, 2003). Some study has indicated that the SNP -93G>A may increase the susceptibility of the promoter sequence to methylation.…”
Section: Discussionmentioning
confidence: 99%
“…Because this polymorphism is located in a CpG island (which occurs at the cytosines of the CpG dinucleotides, and often occurs in clusters), adjacent to CpG cites that are able to undergo methylation (Deng et al, 2001). Goodfellow et al (2003) reported >20% MLH1 gene promoter methylation occurred in a large series of endometrial carcinomas. Chen et al (2007) have showed the variant alleles of SNP -93G>A on MLH1 was associated with MLH1 gene methylation in endometrial and colorectal cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular and epidemiological studies have highlighted key genetic factors in human endometrial tumorigenesis, including loss or epigenetic silencing of the tumor suppressor gene phosphatase and tensin homologue (PTEN) 1 and the DNA mismatch repair (MMR) genes mutL homologue 1 (MLH1), mutS homologue 2 (MSH2) and mutS homologue 6 (MSH6). [2][3][4][5] It is widely accepted that exposure to unopposed estrogen (estrogen in the absence of progesterone) is a potent environmental risk factor for the development of a variety of malignancies, and in particular endometrial carcinoma. [6][7][8] However, deciphering the genes and pathways that are disturbed in estrogen-promoted endometrial cancers has been a difficult task, due in part to the inherent genetic and hormonal heterogeneity that characterizes this tumor type.…”
mentioning
confidence: 99%
“…16 MSI is a molecular feature of approximately one quarter of sporadic human endometrial carcinomas. 5,17,18 Given the histologic and molecular similarities between human endometrial cancers and the lesions that arise in DES-treated mice, we reasoned that the DES murine model was an appropriate experimental system in which to begin to identify genes and genetic networks that are disrupted in estrogen-driven endometrial tumorigenesis. We conducted these studies on genetically homogenous inbred animals, and controlled exposure to the synthetic estrogen in an effort to provide a hormonally homogenous environment in which tumors develop.…”
mentioning
confidence: 99%
“…Furthermore, the majority of MSI-H CRCs occur due to the epigenetic silencing of the MLH1 promoter (4). MMR deficiency has also been shown to give rise to sporadic endometrial cancer with 28% of all endometrial tumours displaying a loss of MMR (5). Moreover, endometrial cancer is also the most common extra-colonic malignancy observed in the Lynch syndrome (6).…”
Section: Introductionmentioning
confidence: 99%